2015
DOI: 10.1038/ncomms6994
|View full text |Cite
|
Sign up to set email alerts
|

Purely hydrodynamic ordering of rotating disks at a finite Reynolds number

Abstract: Self-organization of moving objects in hydrodynamic environments has recently attracted considerable attention in connection to natural phenomena and living systems. However, the underlying physical mechanism is much less clear due to the intrinsically nonequilibrium nature, compared with self-organization of thermal systems. Hydrodynamic interactions are believed to play a crucial role in such phenomena. To elucidate the fundamental physical nature of many-body hydrodynamic interactions at a finite Reynolds n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
89
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 44 publications
4
89
0
Order By: Relevance
“…Moving forward, the flexibility afforded in our design and fabrication processes enables us to easily vary the size and the shape of the micro-rafts and to explore many conceptually interesting questions generic to all self-assembly systems, such as defects, chirality, hierarchy, phase separation, and density-dependent emergent properties ( 41 ). Our long-term vision is to provide a model system for nonequilibrium mechanics that will hold relevance in broader scientific and technological areas.…”
Section: Discussionmentioning
confidence: 99%
“…Moving forward, the flexibility afforded in our design and fabrication processes enables us to easily vary the size and the shape of the micro-rafts and to explore many conceptually interesting questions generic to all self-assembly systems, such as defects, chirality, hierarchy, phase separation, and density-dependent emergent properties ( 41 ). Our long-term vision is to provide a model system for nonequilibrium mechanics that will hold relevance in broader scientific and technological areas.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al studied the hydrodynamics of collectively swimming flagella and observed the formation of dynamic jet-like clusters of synchronously beating flagella [323]. Finally, recent simulations investigated the collective motion of actively rotating disks, which tend to form crystalline structures [357,358].…”
Section: Microswimmers With Hydrodynamic Interactionsmentioning
confidence: 99%
“…It is believed that individual dynamical chirality might be caused by the rotation of the microtubule around its axis [27] or by the special slender shape [28], while interactions between active objects help to align their moving direction [23,26,29]. Besides, man-made catalytical nanorods [30,31], selfmotile colloids [32] or rotating disks [5] can also be dynamically chiral in the form of swimming in circles, and hydrodynamic interaction can synchronize them to form CDC [5]. There is also a recent study of elliptical active particles where particles can rotate in a circular confinement [4].…”
Section: Introductionmentioning
confidence: 99%
“…Collective motion of natural or artificial micro(meso)scopic active objects has attracted growing research interests due to its ubiquity and importance in many systems [1][2][3][4][5][6]. One example is that groups of cells or their fragments can undergo active motion [6][7][8][9][10], and a variety of fundamental processes in development, health and disease depend on such coordinated motions [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%